Engineering of Facets, Band Structure, and Gas‐Sensing Properties of Hierarchical Sn2+‐Doped SnO2 Nanostructures. (9th April 2013) - Wang, Hongkang; Dou, Kunpeng; Teoh, Wey Yang; Zhan, Yawen; Hung, Tak Fu; Zhang, Feihu; Xu, Jiaqiang; Zhang, Ruiqin; Rogach, Andrey L.
Abstract Hierarchical SnO2 nanoflowers, assembled from single‐crystalline SnO2 nanosheets with high‐index (11 <![CDATA[$ \bar 3 $]]> <inline-graphic xlink:href="ark:/27927/pgg3jxvc07n" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) and (10 <![CDATA[$ \bar 2 $]]> <inline-graphic xlink:href="ark:/27927/pgg3jxvc0n8" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) facets exposed, are prepared via a hydrothermal method using sodium fluoride as the morphology controlling agent. Formation of the 3D hierarchical architecture comprising of SnO2 nanosheets takes place via Ostwald ripening mechanism, with the growth orientation regulated by the adsorbate fluorine species. The use of Sn(II) precursor results in simultaneous Sn2+ self‐doping of SnO2 nanoflowers with tunable oxygen vacancy bandgap states. The latter further results in the shifting of semiconductor Fermi levels and extended absorption in the visible spectral range. With increased density of states of Sn2+‐doped SnO2 selective facets, this gives rise to enhanced interfacial charge transfer, that is, high sensing response, and selectivity towards oxidizing NO2 gas. The better gas sensing performance over (10 <![CDATA[$ \bar 2 $]]> <inline-graphic xlink:href="ark:/27927/pgg3jxvc0jm" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) compared to (11 <![CDATA[$ \bar 3 $]]> <inline-graphic xlink:href="ark:/27927/pgg3jxvc0xp" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />) faceted SnO2 nanostructures is elucidated by surface energetic calculations and Bader analyses. This work highlights the possibility of simultaneous engineering of surface energetics and electronic properties of SnO2 based materials.